Comparative Analysis of Slamming Phenomenon Prediction between U and V Hulls using Strip Theory Method - Muhammad Luqman Hakim; Ahmad Firdaus; Gita Marina Ahadyanti; Totok Yulianto (Department of Naval Architecture - Diponegoro University, 2022)
Choosing the right hull shape is important in designing a ship, for example, a U-section or V-section of the hull. The hull shape will affect various aspects, such as design, resistance, seakeeping, structure and production. The ship hull must be properly designed so that it can operate according to the ship’s mission. From the seakeeping aspect of the ship's motion at sea, the difference in the hull shape will result in different motions and dynamic effects such as the slamming phenomenon. Based on the difference in the hull shape cases, this study analyzed the difference in the probability of slamming between the U and V hulls. Both hulls were made based on Formdata and almost all parameters were made the same. Parameters that cannot be forced to be the same are WSA (wetted surface area), (coefficient of waterplane area), and (distance of keel to buoyancy), where those parameters determine the difference in the results. The calculation of RAO (operator amplitude response) was obtained using the strip theory method which assisted by Maxsurf Motion software. The results became the input for the calculation of the slamming probability. The study results show that the U hull has a higher probability of slamming occurrence than that of the V hull, with the difference in values ranging from 20% to 35%. Therefore, the U hull will get more frequent slamming loads, so it has the potential to have a higher structural failure (fatigue) than that of the V hull.